Activity and Selectivity of Cu and Ni Doped TiO2 in the Photocatalytic Reduction of CO2 with H2O Under UV-light Irradiation - He, Z.Q.; Jiang, L.X.; Han, J.; Wen, L.N.; Chen, J.M.; Song, S. (Asian Journal of Chemistry, 2014)
Photocatalysis has been found to be an effective method to convert CO2 into valuable products. To explore the selectivity and photocatalytic activity of transition metal doped TiO2 catalysts for the reduction of CO2, a series of Cu and Ni (0.5-7.0 wt. %) doped TiO2 nanoparticles were prepared by means of a hydrolysis method. Photocatalytic experiments were conducted under irradiation from Hg lamps in a CO2/NaOH aqueous solution. The results indicate that the photoreduction of CO2 with water, catalyzed by Cu-TiO2 and Ni-TiO2, can yield CO, HCHO, CH3OH and CH4. Methane was identified as the major products using Cu-TiO2 or Ni-TiO2. In addition, Ni-TiO2 shows greater CO2 conversion in comparison with Cu-TiO2. With the help of X-ray diffraction, X-ray photoelectron spectroscopy, Brunauer-Emmett-Teller measurements, transmission electron microscopy and UV-visible absorption spectra, it is concluded that both the adsorption and dissociation of CO2 and improvement of the photocatalytic activity by forming a n-p junction and providing matching band potentials, play a crucial role in determining the types and amounts of photoproducts.